A passage to China : literature, loyalism, and colonial Taiwan - Tsai, Chien-hsin, 1975- (Harvard East Asian monographs, 2017)
"Considers the ways in which Taiwan's cession to Japan forever changed Taiwanese writers' and intellectuals' perception of and loyalty to China. Examines the reformulation of traditional Chinese loyalism in colonial Taiwan and the creative ways that select writers employed different genres, mother and foreign tongues, and the notion of ethnicity to accomplish their goals"--